The association between maternal prenatal folic acid and multivitamin supplementation and autism spectrum disorders in offspring: An umbrella review - Biruk Beletew Abate; Biruk Shalmeno Tusa; Ashenafi Kibret Sendekie; Desie Temesgen; Kindie Mekuria; Addis Wondmagegn Alamaw; Molla Azmeraw; Alemu Birara Zemariam; Tegene Atamenta Kitaw; Amare Kassaw; Gebremeskel Kibret Abebe; Befkad Derese Tilahun; et al. (PLoS ONE, 2025)
Background Previous reviews have examined the association between maternal prenatal use of folic acid and multivitamin supplements and autism spectrum disorder (ASD) in children, but findings remain inconclusive. This umbrella review aims to synthesise the existing evidence on the association between prenatal folic acid and multivitamin supplementation and the risk of ASD in offspring. Methods This umbrella review followed the PRISMA guidelines to synthesise and report evidence from existing systematic reviews and meta-analyses (SRMs). Articles were searched in PubMed, Scopus, Web of Science, and Google Scholar. The quality of included studies was assessed using the Assessment of Multiple Systematic Reviews (AMSTAR). A weighted inverse variance random-effects model was applied to estimate pooled effects. The association was quantified using relative risks (RRs) with 95% confidence intervals (CIs). Subgroup analysis and sensitivity analysis were also conducted. Heterogeneity and publication bias were assessed. Results Eight SRMs comprising 101 primary studies and over three million mother-offspring pairs were included. Prenatal folic acid and/or multivitamin supplementation was associated with a 30% reduced risk of ASD in offspring (RR = 0.70, 95% CI: 0.62, 0.78; GRADE: highly suggestive). Subgroup analysis by supplement type showed that maternal prenatal multivitamin supplementation reduced the risk of ASD by 34% (RR = 0.66, 95% CI: 0.55–0.80; GRADE: highly suggestive), while folic acid supplementation was associated with a 30% reduction in ASD risk (RR = 0.70, 95% CI: 0.60–0.83; GRADE: highly suggestive). Conclusion Maternal prenatal folic acid and multivitamin supplementation are associated with a reduced risk of ASD in offspring. These findings have important public health implications, suggesting that prenatal supplementation could help mitigate the risk of ASD in children.